2020
DOI: 10.1038/s41467-020-14584-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for N-terminal acetylation by human NatE and its modulation by HYPK

Abstract: The human N-terminal acetyltransferase E (NatE) contains NAA10 and NAA50 catalytic, and NAA15 auxiliary subunits and associates with HYPK, a protein with intrinsic NAA10 inhibitory activity. NatE co-translationally acetylates the N-terminus of half the proteome to mediate diverse biological processes, including protein half-life, localization, and interaction. The molecular basis for how NatE and HYPK cooperate is unknown. Here, we report the cryo-EM structures of human NatE and NatE/HYPK complexes and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 64 publications
(111 reference statements)
0
47
0
Order By: Relevance
“…Even though AtNAA50 displays catalytic activity on its own, the enzyme might have additional functions in association with the core NatA complex (Deng et al, 2020). This core complex is conserved between humans, yeast, and plants and consists of the catalytic subunit NAA10 and the auxiliary subunit NAA15 (Linster et al, 2015).…”
Section: Nata Activity Is Not Modulated By Naa50mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though AtNAA50 displays catalytic activity on its own, the enzyme might have additional functions in association with the core NatA complex (Deng et al, 2020). This core complex is conserved between humans, yeast, and plants and consists of the catalytic subunit NAA10 and the auxiliary subunit NAA15 (Linster et al, 2015).…”
Section: Nata Activity Is Not Modulated By Naa50mentioning
confidence: 99%
“…The N-terminome profiling approach, however, shows that the depletion of AtNAA50 does not result in decreased acetylation of NatA-type N termini (Table 1), revealing that, unlike ScNAA50, plant NAA50 is not required for the proper function of the NatA complex. Recently, the cryoelectron microscopy structure of the quaternary human NatE/HypK complex was reported and the authors show that HsNAA50 inhibits HsNatA activity in vitro (Deng et al, 2020). In plants, however, the absence of NAA50 does not induce any alteration of NTA on canonical NatA substrates under nonstressed conditions.…”
Section: Nata Activity Is Not Modulated By Naa50mentioning
confidence: 99%
“…Acetyltransferase Activity Assays. All acetyltransferase assays were carried out at room temperature in a reaction buffer containing 75 mM HEPES, pH 7.5, 120 mM NaCl, 1 mM DTT as described [33,34] Cryo-EM data collection. For initial sample screening, 0.6 mg/ml fresh hNatB sample with three-molar excess bisubstrate was used.…”
Section: Protein Expression and Purification Hnaa20 With A C-terminamentioning
confidence: 99%
“…NatC/E/F have overlapping substrates, acting on N-terminal methionine when it is followed by several residues excluding D, E, N and Q [23,[26][27][28][29][30][31]. When another catalytic subunit (NAA50) binds to NatA, a dual enzyme complex NatE is formed [32,33], with catalytic crosstalk between NAA10 and NAA50 [33,34]. We recently demonstrated that both NAA50, and a protein with intrinsic NatA inhibitory activity -Huntingtin-interacting protein K (HYPK) [35][36][37], can bind to NatA simultaneously to form a larger tetrameric complex [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crystal and cryo-EM structures of several NATs have been reported 21,24,[46][47][48][49][50][51][52] , but the structure of the heterotrimeric NatC complex has remained elusive. Here, to obtain insights into the tertiary and quaternary assembly of NatC, we determined its structure by X-ray crystallography and elucidated the mechanism of substrate recognition.…”
mentioning
confidence: 99%